Disclosing in utero HIV/ARV exposure to the HIV‐exposed uninfected adolescent: is it necessary?. Issue 1 (13th October 2016) - Jao, Jennifer; Hazra, Rohan; Mellins, Claude A; Remien, Robert H; Abrams, Elaine J
Abstract : Introduction: The tremendous success of antiretroviral therapy has resulted in a diminishing population of perinatally HIV‐infected children on the one hand and a mounting number of HIV‐exposed uninfected (HEU) children on the other. As the oldest of these HEU children are reaching adolescence, questions have emerged surrounding the implications of HEU status disclosure to these adolescents. This article outlines the arguments for and against disclosure of a child's HEU status. Discussion: Disclosure of a child's HEU status, by definition, requires disclosure of maternal HIV status. It is necessary to weigh the benefits and harms which could occur with disclosure in each of the following domains: psychosocial impact, long‐term physical health of the HEU individual and the public health impact. Does disclosure improve or worsen the psychological health of the HEU individual and extended family unit? Do present data on the long‐term safety of in utero HIV/ARV exposure reveal potential health risks which merit disclosure to the HEU adolescent? What research and public health programmes or systems need to be in place to afford monitoring of HEU individuals and which, if any, of these require disclosure? Conclusions: At present, it is not clear that there is sufficient evidence on whether long‐term adverse effects are associated with in utero HIV/ARV exposures, making it difficult to mandate universal disclosure. However, as more countries adopt electronic medical record systems, the HEU status of an individual should be an important piece of the health record which follows the infant not only through childhood and adolescence but also adulthood. Clinicians and researchers should continue to approach the dialogue around mother–child disclosure with sensitivity and a cogent consideration of the evolving risks and benefits as new information becomes available while also working to maintain documentation of an individual's perinatal HIV/ARV exposures as a vital part of his/her medical records. As more long‐term adult safety data on in utero HIV/ARV exposures become available these decisions may become clearer, but at this time, they remain complex and multi‐faceted.